Differential benthic occupation by crabs in the Ubatuba bay, São Paulo, Brazil - Negreiros-Fransozo, M. L.; Nakagaki, J. M. (Natl Shellfisheries Assoc, 1998)
The goal of this work was to examine the occurrence of brachyurans in soft bottom sublittoral habitats and their association with some environmental factors. The relative abundance of crabs in two depth strata (from 4.5 to 9 m and from 9 to 18 m) was quantified. Crabs were collected with an otter-trawl with 3.7 m of mouth opening and 12-mm mesh in the cod end. Monthly sampling, consisted of a single trawl in each stratum during a 1-yr period, were carried out. Fifteen brachyuran and six anomuran species were found, including Callinectes ornatus Ordway, 1863; Callinectes danae Smith, 1869; Hepatus pudibundus (Herbst, 1785); Libinia spinosa H. Milne-Edwards, 1834; Persephona punctata (Linnaeus, 1758), and P. mediterranea (Herbst, 1794), which were the most abundant and frequent in the area. The most abundant swimming crabs in both strata were C. ornatus and C, dan(re. Size differences in C. ornatus were observed between strata, suggesting a spatial separation of juveniles and adult crabs.
Keywords: ecology; portunid; Callinectes; subtropical region